1999
DOI: 10.1177/0951692899011003005
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Power in the European Union

Abstract: Abstract. In this paper we propose a new method to evaluate the distribution of power between decision making bodies in the European Union. Conventional methods that measure the voting power of players, such as the Banzhaf, Johnston, Holler, and Shapley-Shubik indices, are insufficient for this purpose. They take no account, in an endogenous way, of the differences in the abilities of players to affect the outcome of decision making, which are a result of the existence of political institutions. We propose a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Within non-cooperative game theory assuming one unique equilibrium Steunenberg et al (1999) have suggested a power index based on the distance between a player's ideal point and the equilibrium outcome of a game. Within cooperative game theory power indices are more common (Banzhaf, 1965;Johnston, 1978;Holler, 1984;Shapley, 1953;Shapley and Shubik, 1954).…”
mentioning
confidence: 99%
“…Within non-cooperative game theory assuming one unique equilibrium Steunenberg et al (1999) have suggested a power index based on the distance between a player's ideal point and the equilibrium outcome of a game. Within cooperative game theory power indices are more common (Banzhaf, 1965;Johnston, 1978;Holler, 1984;Shapley, 1953;Shapley and Shubik, 1954).…”
mentioning
confidence: 99%
“…al. 2002;Franchino, 2000;Pollack, 2003b;Steunenberg, Schmidtchen, & Koboldt, 1999). Yet, functionalist approaches have looked at them as channels of expertise, which are detached from political bargaining, and which serve the purpose of efficient problem-solving (Majone, 2005;Scharpf, 1988;Wessels, 1998).…”
Section: Mapping the Institutional Landscape: The Commission's Decisimentioning
confidence: 99%
“…Specifically, how does one find out the spatial dimension or dimensions in terms of which the connected coalitions can subsequently be defined? Steunenberg et al (1999) suggest an approach to power measurement thatalthough similar in spirit to the one proposed by Garret and Tsebelis -runs directly counter with their injunction not to assume random distribution of policy preferences of players. 39 In fact, Steunenberg et al go one step further than the classic power indices in assuming not only that the player coalitions or -in the case of the Shapley-Shubik index -player permutations are equiprobable, but that all states of the world are equally probable.…”
Section: Power and Preferencesmentioning
confidence: 99%